Antigenic properties estimation for legumain protein recombinant analogue of trematoda Opisthorchis felineus, causing human opisthorchiasis - I. A. Razumov; M. N. Lvova; Ye. P. Ponomareva; A. V. Katokhin; V. A. Petrenko; A. E. Sazonov; L. M. Ogorodova; V. V. Novitsky; A. Yu. Sivkov; V. A. Mordvinov (Бюллетень сибирской медицины, 2012)
We estimated potential of protein legumain from opisthorchiasis agent O. felineus for application in immunodiagnosis of this disease. Bacterially expressed recombinant protein (rOF49-leg) showed strong difference in Enzyme-linked immunosorbent assay (ELISA) between infected and negative sera. These results suggest the potential of this antigen for development of serodiagnostic test for human opisthorchiasis.